Keanekaragaman Jamur Makroskopis Di Kawasan Hutan Mangrove Karang Sungai Pisang Kecamatan Teluk Kabung Kota Padang Sumatera Barat - Kurnia Putri Indrawan; Dezi Handayani (Jurnal Serambi Biologi, 2022)
Indonesia is a mega-biodiversity country, one of the most abundant biodiversity is fungi or mushrooms. Fungi or fungi are generally classified into two types, namely microscopic fungi and macroscopic fungi. Mangrove forests are ideal habitats for fungi because of the characteristics of the area which is always moist. This study aims to determine the types of macroscopic fungi in the Karan Sungai Pisang Mangrove Forest, Teluk Kabung District, Padang City, Sumatra. This study used a random roaming method in the mangrove forest area and the technique of collecting samples was incidental. The results obtained 9 types of mushrooms, namely: Irpex lacteus, Auricularia auricular, Myxarium sp., Lentinus sajor caju, Trametes sp. 1, Trametes sp. 2, Rigidoporus sp., Ganoderma lucidum, and Daldinia concentrica. These mushrooms belong to 6 families, namely: Phanerochaetaceae, Auriculariaceae, Hyaloriaceae Poliporaceae, Ganodermaceae, and Xylariaceae.